Psychological skills training of an elite wheelchair water-skiing athlete: a single-case study - de Bressy de Guast, V.; Golby, J.; Van Wersch, A.; d'Arripe-Longueville, F. (Adapted Physical Activity Quarterly, 2013)
This study presents a complete psychological skills training (PST) program with a wheelchair athlete and examines the program effectiveness using a mixed-method approach. After initial testing, the athlete followed a two-month program of selfconfidence building, motivational, visualization/relaxation, and injury management techniques. Quantitative and qualitative methods were used to examine the impacts on performance and psychological abilities. The triangulated results suggest that the PST program was perceived as effective by the athlete in terms of his sporting performances and mental skills. The characteristics and implications of a PST program with this wheelchair athlete are discussed, as well as the study limitations and the perspectives for future research